Effects of the Active Smarter Kids (ASK) Physical Activity School-based Intervention on Executive Functions: A Cluster-Randomized Controlled Trial. Issue 2 (23rd February 2019) - Aadland, Katrine Nyvoll; Ommundsen, Yngvar; Anderssen, Sigmund Alfred; Brønnick, Kolbjørn Selvåg; Moe, Vegard Fusche; Resaland, Geir Kåre; Skrede, Turid; Stavnsbo, Mette; Aadland, Eivind
ABSTRACT: The purpose of this study was to examine the effects of a seven-month curriculum prescribed physical activity (PA) intervention (the Active Smarter Kids [ASK] intervention) on executive functions in 10-year-old Norwegian children. A linear mixed model was used to analyze data from 971–1, 123 fifth grade children at 28 intervention schools and 29 control schools. The intervention constituted three PA elements: PA educational lessons, PA breaks, and PA homework, adding 165 minutes of PA to the mandatory 135 minutes of PA and physical education. There was no effect of the intervention on executive functions in the intention-to-treat analyses. Per protocol analyses ( n  = 776–850) revealed small effects of the intervention on the composite score of executive functions, cognitive flexibility, and motor skills. Cognitively engaging and coordinative demanding activities/games seem viable options to increase executive functions and possibly improve academic performance in children.